2022
DOI: 10.1155/2022/3477886
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive Bond Integrity of Experimental Zinc Oxide Nanoparticles Incorporated Dentin Adhesive: An SEM, EDX, μTBS, and Rheometric Analysis

Abstract: Objective. Our study is aimed at preparing an experimental adhesive (EA) and assessing the influence of adding 5-10 wt.% concentrations of zinc oxide (ZnO) nanoparticles on the adhesive’s mechanical properties. Methods. Field emission scanning electron microscopy (FESEM) and energy dispersive X-ray (EDX) spectroscopy were employed to investigate the morphology and elemental distribution of the filler nanoparticles. To examine the adhesive properties, microtensile bond strength (μTBS) testing, an investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
2
0
0
Order By: Relevance
“…Regarding failure types at the interface, we observed cohesive failures (adhesive‐dentin) to be the most common in our study. Our study's findings confirmed the outcomes of earlier research in which adhesive‐dentin type failure was most frequently noted following the addition of filler NPs in the adhesive (Alfaawaz et al, 2022; Alqarawi et al, 2021). Given that bonding the adhesive with dentin is a challenging process, the collagenous composition of dentin and its moist environment may have played a significant role in observing this sort of failure (Peumans et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding failure types at the interface, we observed cohesive failures (adhesive‐dentin) to be the most common in our study. Our study's findings confirmed the outcomes of earlier research in which adhesive‐dentin type failure was most frequently noted following the addition of filler NPs in the adhesive (Alfaawaz et al, 2022; Alqarawi et al, 2021). Given that bonding the adhesive with dentin is a challenging process, the collagenous composition of dentin and its moist environment may have played a significant role in observing this sort of failure (Peumans et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Regarding failure types at the interface, we observed cohesive failures (adhesive-dentin) to be the most common in our study. Our study's findings confirmed the outcomes of earlier research in which adhesive-dentin type failure was most frequently noted following the addition of filler NPs in the adhesive (Alfaawaz et al, 2022;Alqarawi et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, Alfaawaz et al [42] conducted an experiment wherein they developed an adhesive and examined how the addition of ZnO NPs at concentrations of 5-10 wt.% affects the mechanical properties of the adhesive. The addition of ZnO NPs at concentrations of 5 and 10 wt.% enhanced the adhesive's microtensile bond strength (μTBS).…”
Section: Zinc Oxide Nps (Zno Nps)mentioning
confidence: 99%
“…The addition of ZnO NPs at concentrations of 5 and 10 wt.% enhanced the adhesive's microtensile bond strength (μTBS). Nevertheless, a decrease in viscosity was noted for both adhesives reinforced with NPs [42] According to a study conducted by Spencer et al [43], ZnO was added into Fuji Ortho LC (Tokyo, Japan) to produce mixes containing 13% ZnO and 23.1% ZnO. The adjusted adhesive agent was subjected to incubation with S. mutans for 48 hours in a diffusion disc experiment, which was employed to quantify the areas of bacterial suppuration.…”
Section: Zinc Oxide Nps (Zno Nps)mentioning
confidence: 99%